Значення ізотопів вуглецю для вирішення проблем генези родовищ корисних копалин - Сворень, Й. (Геологія і геохімія горючих копалин, 2010)
Доказано, що зміна-диференціація ізотопного складу вуглецю в гідротермальних карбонатах і діамантах залежить як від різної хімічної активності його ізотопів
відносно різних елементів, зокрема катіонів кальцію і міді, так і тривалості повільного процесу синтезу кристалів, який протікає при мінімумі ентропії системи в дифузійних умовах, тобто, встановлено раніше невідому більшу хімічну активність 13С
(важчого ізотопу вуглецю) у процесах утворення цих карбонатів, діамантів та інших
вуглецьвмісних твердих тіл та легкого ізотопу вуглецю у процесах синтезу летких
компонентів, зокрема метану.
Важкі діаманти з кімберлітів південних діамантовмісних районів Якутії належать до ультраосновного-кімберлітового парагенезису, а легкі, які частіше знаходять у розсипах північних районів, − до еклогітового. Під час росту-формування
кристалів діаманта відбувається диференціація ізотопів вуглецю із його поважчанням. Диференціацію ізотопів вуглецю в природі експериментально промодельовано
процесами синтезу кристалів СаСО3
, Сu2
(ОН)2
СО3
.
Поданими результатами й іншими тут не представленими стверджується, що
планета Земля побудована в різні часи із двох різних за походженням вуглецьвмісних утворень-порід: 1 – розплавної частини, названої астеносферою, та 2 – літосфери Землі, що в часі пізніше оповила астеносферу, які разом і створили нашу планету
з нинішніми параметрами на орбіті та сприятливими умовами для життя на ній. Така
була Воля Творця Всесвіту! It was proved that alteration-differentiation of the isotope composition of carbon in
hydrothermal carbonates and diamonds depends both upon different chemical activity of
its isotopes in relation to different elements, particularly cations of calcium and copper,
and duration of a gradual process of the crystal synthesis occurring at minimum entropy
of the system under diffusion conditions, that is to say, the greater chemical activity of 13C
(heavy isotope of carbon), unknown before, was established in the process of the formation of these carbonates, diamonds and other carbon-containing solid bodies and light
isotope of carbon in the process of synthesis of volatile components, methane in particular.
Hard diamonds from kimberlites of the southern diamond-containing regions of Yakutia are related to ultra-basic kimberlite paragenesis, but light diamonds that are usually
found in deposits of the northern regions, are related to eclogite paragenesis. During the
growth-formation of diamond crystals, the differentiation of carbon isotopes with its heavy
139
growth occurs. By processes of synthesis of crystals of CaCO3 and Cu2(OH)2CO3 we have
modelled experimentally the differentiation of carbon isotopes in nature.
Methane in form of the existence of Ca(OH)2 · CH4 with water steam and temperature
>580 °C transfers these and other constituents of fluid at great distances, which:
–– mineralizes pore spaces, fractures of different size etc., which with decrease in
temperature become healed-cemented by carbonates that by their defects trap the carbonate-forming environment itself together with CH4. The screens-covers of wasp, in which
oil and gas are preserved up to now, are formed-constructed in a similar way;
–– being transformed adiabatically into sedimentary rocks with a thick layer of organic remains, it exposes them to strong physical-chemical influence from one side-direction, heats them to temperatures 700–800 °C, at which they are initial stage of heating
leave the area of future seam up to the time of coal formation. As methane has come from
the fracture, then its concentration in the direction to it should increase and in the final case
should be associated with a gas deposit-field. Coal methane itself has a double abiogenicbiogenic nature with pre-dominance of the abiogenic part which in hermetically well covermineralized coal seam and newly deposited minerals and rocks can be under abnormally
high pressure.
Submitted results and those, non-submitted here, allow us to confirm that the Earth
planet was formed in different times from two carbon-containing rock formations of different origin: the first- from a molten part called astenosphere, and the second- from the
lithosphere of the Earth which later wrapped the astenosphere that together they have created our planet with present parameters in the orbit and favourable conditions for life in it.
Such was a will of the creator of the world!